Targeting self- and foreign antigens to dendritic cells via DC-ASGPR generates IL-10–producing suppressive CD4(+) T cells - Li, Dapeng (The Rockefeller University Press, 2012)
Dendritic cells (DCs) can initiate and shape host immune responses toward either immunity or tolerance by their effects on antigen-specific CD4(+) T cells. DC-asialoglycoprotein receptor (DC-ASGPR), a lectinlike receptor, is a known scavenger receptor. Here, we report that targeting antigens to human DCs via DC-ASGPR, but not lectin-like oxidized-LDL receptor, Dectin-1, or DC-specific ICAM-3–grabbing nonintegrin favors the generation of antigen-specific suppressive CD4(+) T cells that produce interleukin 10 (IL-10). These findings apply to both self- and foreign antigens, as well as memory and naive CD4(+) T cells. The generation of such IL-10–producing CD4(+) T cells requires p38/extracellular signal-regulated kinase phosphorylation and IL-10 induction in DCs. We further demonstrate that immunization of nonhuman primates with antigens fused to anti–DC-ASGPR monoclonal antibody generates antigen-specific CD4(+) T cells that produce IL-10 in vivo. This study provides a new strategy for the establishment of antigen-specific IL-10–producing suppressive T cells in vivo by targeting whole protein antigens to DCs via DC-ASGPR.